Successful affiliate marketing for merchants - Fiore, Frank, 1946- (Que, 2001)
If you¿re an online business, instead of paying for an ad, like a banner, you pay for the result - the sale. This is called affiliate marketing. Pay for Performance will show anyone conducting business online, how to plan, implement, and manage a successful affiliate marketing program. The reader will find valuable Web resources such as tracking software and contract templates with the guidance of this book. There will also be direction for the reader to focus the content and develop the right affiliate model for the type of business. It will also provide case studies of successful programs as well as failures and scams to demonstrate and teach the lessons of building a successful program.